The Smart Parenting in Overcoming Social withdrawal to Students at the Asy-Syaikh Abdurrahman Jambon Ungaran Islamic Boarding School - Barokah, Laeli; Isnaini, Isnaini; Adibah, Ida Zahara (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to explore the implementation of smart parenting in overcoming social withdrawal among students at the Asy-Syaikh Abdurrahman Jambon Islamic boarding school, Ungaran, where the phenomenon of social withdrawal or withdrawing from social interaction has become a new challenge in the Islamic boarding school environment. This research uses a qualitative approach with in-depth interview techniques, participant observation, and documentation. The research results show that smart parenting, which emphasizes emotional understanding, positive communication, and child empowerment, is effective in helping students emerge from social isolation. This approach involves strengthening religiosity, developing social skills, and providing gradual psychological support. Implementing smart parenting increases student's openness and self-confidence and strengthens the emotional relationship between students and caregivers. These findings are an important contribution to developing parenting strategies in the Islamic boarding school environment.